2021
DOI: 10.1186/s12891-021-04032-y
|View full text |Cite
|
Sign up to set email alerts
|

Gravity determines the direction of nerve roots sedimentation in the lumbar spinal canal

Abstract: Objectives To investigate the role of gravity in the sedimentation of lumbar spine nerve roots using magnetic resonance (MR) imaging of various body positions. Methods A total of 56 patients, who suffered from back pain and underwent conventional supine lumbar spine MR imaging, were selected from sanmen hospital database. All the patients were called back to our hospital to perform MR imaging in prone position or lateral position. Furthermore, the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
(3 reference statements)
0
0
0
Order By: Relevance
“…Yang et al [6] demonstrated that nerve root position is affected by gravity during MRI examiantion. In the present study, all the patients were examined in the supine position; however, not all the patients had nerve roots in the same position.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Yang et al [6] demonstrated that nerve root position is affected by gravity during MRI examiantion. In the present study, all the patients were examined in the supine position; however, not all the patients had nerve roots in the same position.…”
Section: Discussionmentioning
confidence: 99%
“…of nerve roots Infront of the intertransverse process of L3, however; there was decreased reading of P value as we are moving down the table to started as0.427 in cases of single level prolapse to decrease gradually in the other conditions namely, the multiple prolapses and multiple bulges to start to has a statistically significant difference in the lower 3 pathological conditions as we mentioned above. Yang et al [6] demonstrated that nerve root position is affected by gravity during MRI examiantion. In the present study, all the patients were examined in the supine position; however, not all the patients had nerve roots in the same position.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations